Investigation of PAH and oil degradation along with electricity generation in soil using an enhanced plant-microbial fuel cell. (1st June 2019) - Zhao, Lin; Deng, Jinghui; Hou, Huijie; Li, Jingchen; Yang, Yongkui
Abstract: From extraction to use, crude oil undergoes a series of processes such as transportation and refining that inevitably lead to the contamination of soil by the oil. The conventional bioremediation of petroleum in soil is circumscribed by the low activity of functional microbes, scarcity of electron acceptors, and inefficient electron transfer. This study investigated the effects and mechanism of plants, carbon sources, and surfactants on petroleum and polyaromatic hydrocarbon (PAH) degradation using enhanced plant-microbial fuel cells (P-MFCs) in soil. The degradation rate of PAHs (phenanthrene and pyrene) significantly increased with increasing surfactant concentration and the addition of plants. Compared with the co-metabolism of glucose, the addition of β-cyclodextrin more strongly enhanced oil remediation in soil. The charge-transfer resistance values in the MFCs were significantly reduced with the addition of plants, glucose, and β-cyclodextrin. The synergistic action of the plants and surfactants significantly enhances the efficiency of the MFC system in the removal of petroleum from soil, and recommends the applications of P-MFCs for the in situ remediation of petroleum-contaminated soils. Graphical abstract: Image 1 Highlights: An enhanced plant-microbial fuel cell (MFC) was designed for oil degradation in soil. Plants, glucose, and cyclodextrin significantly reduced resistance in the MFC. Surfactant solubilization of oil was more effective than glucose co-metabolism. Synergy of plants and surfactants significantly improved MFC's oil removal from soil.